Usurpação inconstitucional de competência no âmbito dos tribunais: uma análise crítica da atuação jurisdicional extra legem no controle difuso de constitucionalidade - Gonçalves, Caio Rodrigues (2021)
After the advent of post-positivism and neoconstitutionalism, the Judiciary became the locus for discussion of moral and political controversies that, in the past, were decided by the popular participation in its direct or indirect form. The constitutionalist movement, by guaranteeing a central role for constitutions in the construction and solidification of the legal and political pillars of Western societies, enabled the institutional inflation of the Judiciary (especially of constitutional courts) and, consequently, also the emergence and expansion of two phenomena central to the redefinition of the democratic pact: judicial activism and the judicialization of politics. These phenomena directly influence the exercise of judicial review, whether in the diffuse way or in the concentrated way. This work will carry out an immersion in the consequences of non-observance of the specific constitutional procedure foreseen for the declaration of unconstitutionality of laws or normative acts of the Public Power in the diffuse way: the full bench rule. Therefore, the origin of the full bench rule in Brazil will be studied, as well as the main causes for its non-compliance, so that, in the end, it will be possible to establish a possible solution based on institutional dialogue. The methodology consisted, initially, in the survey and analysis of doctrinal texts contained in the references of this study (qualitative nature), characterized by a bibliographic bias. At the end, to verify the damage caused by non-compliance with the specific plenary reserve clause, the hypothetical-deductive methodology was used.